2023
DOI: 10.1001/jama.2023.8073
|View full text |Cite
|
Sign up to set email alerts
|

Recent Vitamin K Antagonist Use and Intracranial Hemorrhage After Endovascular Thrombectomy for Acute Ischemic Stroke

Abstract: ImportanceUse of oral vitamin K antagonists (VKAs) may place patients undergoing endovascular thrombectomy (EVT) for acute ischemic stroke caused by large vessel occlusion at increased risk of complications.ObjectiveTo determine the association between recent use of a VKA and outcomes among patients selected to undergo EVT in clinical practice.Design, Setting, and ParticipantsRetrospective, observational cohort study based on the American Heart Association’s Get With the Guidelines–Stroke Program between Octob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…However, recent VKA use with an INR >1.7 was associated with a significantly increased risk of sICH compared with the non‐VKA patients. 8 These findings provide practical information to select appropriate therapeutic strategies for AIS patients pretreated with VKA and offer access to EVT therapy for more anticoagulated patients.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…However, recent VKA use with an INR >1.7 was associated with a significantly increased risk of sICH compared with the non‐VKA patients. 8 These findings provide practical information to select appropriate therapeutic strategies for AIS patients pretreated with VKA and offer access to EVT therapy for more anticoagulated patients.…”
mentioning
confidence: 84%
“…In the issue of JAMA on June 20, 2023, Brian Mac Grory and colleagues 8 investigated the association between VKA use within the 7 days preceding hospital admission and the occurrence of sICH within 36 h among 32,715 patients undergoing EVT in 594 hospitals. Overlap weighting, a propensity score weighting method, was employed to achieve a precise balance in covariates between patients who were either taking or not taking a VKA.…”
mentioning
confidence: 99%
“…This association was not found in DOAC patients. A newly published register-based study found recent use of VKA to significantly increase the risk of sICH (8.3%) after EVT if INR was higher than 1.7, compared with OAC-naïve patients [75]. DOAC treatment has also been associated with increased rates of successful reperfusion and better functional outcomes after EVT compared to VKA [76].…”
Section: Use Of Evt In Atrial Fibrillationmentioning
confidence: 99%
“…To the Editor I have some concerns about the recent article that investigated whether recent exposure to vitamin K antagonists (VKAs) in patients with acute ischemic stroke selected to undergo endovascular thrombectomy (EVT) increased the risk of symptomatic intracranial hemorrhage (sICH).…”
mentioning
confidence: 99%